2018
DOI: 10.1016/j.ijppaw.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of alien freshwater fishes in Patagonia (Argentina)

Abstract: A survey of the helminth parasites of alien freshwater fishes from Argentinean Patagonia is presented, based on samples taken from 2010 to 2017 and including previous published records. A total of 1129 fishes were collected, belonging to 11 species from 7 families. We surveyed 34 localities in 12 river basins, and found 43 parasite taxa (15 digeneans, 14 monogeneans, 5 cestodes, 5 nematodes, and 4 acanthocephalans), belonging to 22 families. Data are presented as a parasite/host list with information on host s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
(81 reference statements)
0
9
0
1
Order By: Relevance
“…In this regard, Rauque et al . (2018) suggested that exotic salmonids stand out as hosts which are highly susceptible to infection by the parasites of Patagonian native fish; this leads to an increase in native parasite populations, as observed for A. tumescens (Rauque et al ., 2003). The rate of experimental transmission of D. lacustris (19.2%) was lower than that registered for A. tumescens transmitted between G. maculatus and O. mykiss in Patagonia (37% in Rauque et al ., 2002; 21.8% in Paterson et al ., 2013).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this regard, Rauque et al . (2018) suggested that exotic salmonids stand out as hosts which are highly susceptible to infection by the parasites of Patagonian native fish; this leads to an increase in native parasite populations, as observed for A. tumescens (Rauque et al ., 2003). The rate of experimental transmission of D. lacustris (19.2%) was lower than that registered for A. tumescens transmitted between G. maculatus and O. mykiss in Patagonia (37% in Rauque et al ., 2002; 21.8% in Paterson et al ., 2013).…”
Section: Discussionmentioning
confidence: 91%
“…The following native fishes have been reported as definitive hosts: Galaxias maculatus (Jenyns, 1842), Galaxias platei Steindachner, 1898 (Galaxiidae), Olivaichthys viedmensis (MacDonagh, 1931) (Diplomystidae) and Percichthys trucha (Valenciennes, 1833) (Percichthyidae) (Shimazu et al ., 2000; Tsuchida et al ., 2021 a ). The following introduced fishes have also been reported as definitive hosts: Oncorhynchus mykiss (Walbaum, 1792), Salmo salar Linnaeus, 1758, Salmo trutta Linnaeus, 1758, and Salvelinus fontinalis (Mitchill, 1814) (Salmonidae) (Shimazu et al ., 2000; Rauque et al ., 2018; Tsuchida et al ., 2021 a ). Salmonids were introduced from the USA into Patagonian freshwater environments as embryonated eggs at the beginning of the 20th century (Tulián, 1908).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016), Eiras (2016), Rauque et al . (2018)). These are larger internal parasites, of which several can be observed with the naked eye in infected fish (Jansson & Vennerström, 2014).…”
Section: Diseases Of Lumpfish and Wrassementioning
confidence: 99%
“…Known parasitic helminths of fish are different species of nematodes (roundworms), flukes and cestodes (tapeworms) (e.g. see Bristow (1993), Jyrwa et al (2016), Eiras (2016), Rauque et al (2018)). These are larger internal parasites, of which several can be observed with the naked eye in infected fish (Jansson & Vennerstr€ om, 2014).…”
Section: Parasitesmentioning
confidence: 99%